Strategi, Tantangan, dan Peluang Reaktualisasi Nilai-nilai Ilmu Sosial Profetik dalam Perspektif Agribisnis Peternakan: Pendekatan Konseptual-Teoritis - Husna, Mustafid; Yunasaf, Unang; Sulistyati, Marina (Universitas Galuh, 2026)
Livestock agribusiness faces various structural issues, demonstrating the need for a more comprehensive approach, not only technical but also social aspects, ethics, and moral values. Kuntowijoyo's prophetic social science, consisting of the pillars of humanization, liberation, and transcendence, offers a potential ethical and social framework for transforming livestock agribusiness practices and governance. This study uses a qualitative conceptual-theoretical approach with a literature review method to examine livestock agribusiness from a prophetic social science perspective and analyze its strategies, challenges, and opportunities. The results of the study indicate that livestock agribusiness from a prophetic social science perspective consists of the pillars of humanization (towards livestock workers, livestock, and consumers), liberation (from economic oppression, backwardness and powerlessness), and transcendence (spiritual intentions-goals, moral-ecological responsibility, and social distribution-justice). Reactualization strategies include increasing livestock farmer capacity, strengthening animal welfare regulations, empowering livestock farmers, strengthening organizational structures, fostering shared values, market chain reform, inclusive access to capital, moral reform, strengthening halal-thayyib ethics, and sustainable governance based on ethical, civilized, and spiritual values. Key challenges include weak ethical and technological literacy, unequal market structures, ineffective policies, and the low integration of moral values into livestock agribusiness practices. Opportunities include the development of digital technology, increased awareness of ethics, halal certification, and animal welfare issues, the development of productive livestock-based philanthropy, and support for sustainable policies. This study provides that the reactualization of prophetic values can be an important paradigm in building a more humane, ethical, equitable, and spiritually based livestock agribusiness, thereby creating social transformation.